Factores que favorecieron la implementación proyecto de turismo rural comunitario desarrollado por la asociación de turismo vivencial “Raíces Inkas”, bajo el modelo asociativo, en la ciudad de Cusco, periodo 2018-2019 - Zaldívar Díaz, Saby Elizabeth (2024)
Within tourism trends, we find a strong inclination towards responsible travel, which seeks alternatives to sustainable destinations and has a preference for places committed and friendly to the development of the environment, whether social or natural. Live experiences bring together the main initiatives that Peru presents as sustainable, competitive and authentic tourism products. These, in turn, are part of the products called Community Rural Tourism, created by MINCETUR (Ministry of Foreign Trade and Tourism). This type of tourism does not have much time running in our country and therefore faces certain challenges that contemplate the implementation and understanding of the operation and commercialization of the product by those involved, that is, the management of the ventures, in this case Local communities and families. Given that there are different ventures of this type of tourism at the national level, the Experiential Tourism Association "Raíces Inkas" stands out among many, first, for its validity over time; It has been operating for 18 years being a great reference for new initiatives. The Association is located in the Community of Raqchi, in the department of Cusco, where other enterprises in different degrees of development already live together. The present investigation investigates the main factors that have made the Experiential Tourism Association “Raíces Inkas” a successful case. To do this, we will know what favored the implementation of the Community Rural Tourism project through the actions developed by the Association and analyzing the processes, strategies applied, the promotion of community participation, the improvement of the quality of life and the consideration of the intercultural approach, which will allow us to propose measures to improve and strengthen the project. The investigation period covers the years 2018-2019, the case study was assumed as a way of approaching the investigation and the qualitative methodology was used, based mainly on the investigation, as well as the quantitative methodology. For the collection of the information, the interview, survey and observation techniques were used, achieving an analysis on the participation of the actors involved, the management of the venture, its potential, future plans and thanks to the use of these techniques the unknowns were resolved that originated the investigation. The research findings show that the association has taken advantage of the opportunities offered by its strategic location, through the implementation of a model of Community Rural Tourism (TRC), which in addition to its other main activities such as agriculture and sale of handicrafts, has managed to improve its economy and quality of life. The co-management of the association was evidenced by the presence of other public and private institutions involved in the development of the project. The research indicates that there are actions to improve like to create and strengthen the use of management documents, as well as develop the management capacities of the beneficiaries, achieving the strengthening of the association's human and social capital, strengthening the monitoring and control of the actions implemented as part of the various training received, improve the income distribution model, expand the promotion of the association and thus optimize the co-management and tourism activity in the community to achieve a greater impact in favor of the local economy.